Value and distribution : - Davenport, Herbert Joseph (Augustus M. Kelly, 1964)
The emphasisin the present volume upon the entrepreneur point of view in the computation of costs and in the analysis of the process by which distributive shares are assigned, has nothing new in it; it was nescessary only that the point of view be clearly distinguished, consistently held, and fully developed.